Theaters of Anatomy Students, Teachers, and Traditions of Dissection in Renaissance Venice - Klestinec, Cynthia (Johns Hopkins University Press, 2011)
Of enduring historical and contemporary interest, the anatomy theater is where students of the human body learn to isolate structures in decaying remains, scrutinize their parts, and assess their importance. Taking a new look at the history of anatomy, Cynthia Klestinec places public dissections alongside private ones to show how the anatomical theater was both a space of philosophical learning, which contributed to a deeper scientific analysis of the body, and a place where students learned to behave, not with ghoulish curiosity, but rather in a civil manner toward their teachers, their peers, and the corpse. Klestinec argues that the drama of public dissection in the Renaissance (which on occasion included musical accompaniment) served as a ploy to attract students to anatomical study by way of anatomy's philosophical dimensions rather than its empirical offerings. While these venues have been the focus of much scholarship, the private traditions of anatomy comprise a neglected and crucial element of anatomical inquiry. Klestinec shows that in public anatomies, amid an increasingly diverse audience-including students and professors, fishmongers and shoemakers-anatomists emphasized the conceptual framework of natural philosophy, whereas private lessons afforded novel visual experiences where students learned about dissection, observed anatomical particulars, considered surgical interventions, and eventually speculated on the mechanical properties of physiological functions. Theaters of Anatomy focuses on the post-Vesalian era, the often-overlooked period in the history of anatomy after the famed Andreas Vesalius left the University of Padua. Drawing on the letters and testimony of Padua's medical students, Klestinec charts a new history of anatomy in the Renaissance, one that characterizes the role of the anatomy theater and reconsiders the pedagogical debates and educational structure behind human dissection.